Cover Picture: Aerogels with 3D Ordered Nanofiber Skeletons of Liquid‐Crystalline Nanocellulose Derivatives as Tough and Transparent Insulators (Angew. Chem. Int. Ed. 39/2014). Issue 39 (17th July 2014) - Kobayashi, Yuri; Saito, Tsuguyuki; Isogai, Akira
<x xml:space="preserve">Abstract</x> Aerogels with 3D‐ordered nanofiber skeletons of liquid‐crystalline nanocellulose are described by T. Saito et al. in their Communication on page 10394 ff. The nanocellulose is composed of mechanically strong, surface‐carboxylated cellulose nanofibers dispersed in a nematic order, which were prepared from abundant wood biomass through a water‐based process. These aerogels display good insulation properties, optical transparency, and mechanical toughness.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>